Penerapan Metode Kompetisi dalam Proses Pembelajaran pada Peserta Didik Sekolah Negeri 060880 Medan Polonia - Intan Maghdalena; Fajar Utama Ritonga; Berlianti, Berlianti (Yayasan Literasi Sains Indonesia, 2023)
The learning process is essentially a process of interaction between teachers and learners, the process is the delivery of messages from teachers through certain media to the recipient of the message or learners. In the process of learning an educator must try to achieve the goal as much as possible. One of these efforts is to use teaching methods, educators who teach using effective and efficient methods can heighten the interest and attention of learners and achieve learning goals. One method that can be applied as an educator is the Competitive Based Learning method, which is a learning method that utilizes competition or competition to increase learning interest, and measure the success rate of learning that has been done by students or learners. The purpose of community service activities apart from fulfilling the fieldwork practices assignments is to help increase the motivation of learners towards learning in the classroom. With the application of the competition method has a positive impact so as to make students more motivated in following the learning, this can be seen from the enthusiasm and courage of the students of Sekolah Dasar Negeri 060880 Medan Polonia.